Rheumatologic complications in a cohort of 227 patients with common variable immunodeficiency. (18th April 2018) - Azizi, G.; Kiaee, F.; Hedayat, E.; Yazdani, R.; Dolatshahi, E.; Alinia, T.; Sharifi, L.; Mohammadi, H.; Kavosi, H.; Jadidi‐Niaragh, F.; Ziaee, V.; Abolhassani, H.; et al.
Abstract: Common variable immunodeficiency (CVID) is the most prevalent symptomatic type of human primary immunodeficiency diseases (PID). Clinically, CVID is characterized by increased susceptibility to infections and a wide variety of autoimmune and rheumatologic disorders. All patients with CVID registered in Iranian PID Registry (IPIDR) were enrolled in this retrospective cohort study. We investigated the frequency of rheumatologic diseases and its association with immunological and clinical phenotypes in patients with CVID. A total of 227 patients with CVID were enrolled in this study. The prevalence of rheumatologic disorders was 10.1% with a higher frequency in women than men. Most common rheumatologic manifestations were juvenile idiopathic arthritis (JIA) and adult rheumatoid arthritis (RA) followed by juvenile spondyloarthritis (JSpA) and undifferentiated inflammatory arthritis (UIA). Septic arthritis in patients with CVID with a history of RA and JIA was higher than patients without rheumatologic complication. Patients with CVID with a history of autoimmunity (both rheumatologic and non‐rheumatologic autoimmunity) had lower regulatory T cells counts in comparison with patients without autoimmune disorders. There was an association between defect in specific antibody responses and negative serologic test results in patients with rheumatologic manifestations. JIA, RA, JSpA and UIA are the most frequent rheumatologic disorders in patients with CVID. Due to antibody deficiency, serologic tests may be negative in these patients. Therefore, these conditions pose significant diagnostic and therapeutic challenges for immunologists and rheumatologists in charge of the care for these patients.